Human Needs Are Unlimited In The Perspective Of Sharia Economics (Homo Economicus Vs Homo Islamicus) - Dwiatmaja, Ahmad Zikri; Abdullah, Muhammad Wahyuddin; Ayu Parmitasari, Rika Dwi; Dana Kusuma, Suteja Wira (Likuid Jurnal Ekonomi Industri Halal, 2025)
This research aims to explore the assumptions underlying the concept of Homo Islamicus in the context of modern society's shifting preferences, where the concept of Homo Economicus, which tends to disregard morality and focuses on self-interest in maximizing utility, falls short in explaining these phenomena. By examining Homo Islamicus in the modern context, this study seeks to identify assumptions more relevant to current economic conditions. The research adopts a library research method and utilizes content analysis as the data processing technique. The findings reveal that the concept of Homo Islamicus integrates moral and rational elements in a balanced proportion, oriented towards general welfare aligned with individuals' basic needs, guided by religious moral principles. Rational decisions made by Homo Islamicus reflect moral values based on fundamental principles such as Tawhid (Unity of God), Balance, Free Will, Responsibility, and Justice, enabling decision-making that considers these values. Thus, morality serves as the foundation of rationality in making choices within the context of modern Islamic economics.